Thermoelectric Devices: A Review of Devices, Architectures, and Contact Optimization - He, Ran; Schierning, Gabi; Nielsch, Kornelius (Advanced Materials Technologies, 2018)
In recent years, the substantially improved performance of thermoelectric (TE) materials has attracted considerable interest in studying the potential applications of the TE technique. Serving as the bridge between TE materials and applicable TE products, TE devices must be properly designed, engineered, and assembled to meet the required performance of TE products for cooling (thermoelectric cooler) and power generation (thermoelectric generator). The principle feasibility of the TE technique has been demonstrated using a variety of different materials and processing technologies, and many different architectures of TE devices have been successfully realized. This review discusses the architectures of TE devices, including bulk and thin-film TE devices, TE devices with flexible designs, pn-junction-based TE devices that provide robust solutions for high operation temperatures, and the meta-material-based transverse TE devices. In addition, the assembly of TE devices involves contact layers on which the reliability of TE devices depends. Thus solutions to contact issues, including bonding strength, contact resistance, and thermomechanical stress, are also reviewed.
CRIS-Team Scopus Importer:2022-04-14
Keywords: contact; device architectures; thermoelectric coolers; thermoelectric devices; thermoelectric generators